THE USE OF ACADEMIC VOCABULARY IN DIFFERENT ACADEMIC DISCIPLINES (Intent Research Scientific Journal, 2024)
This article explores the critical role of academic vocabulary within academic disciplines. It examines how academic vocabulary is defined by scholars and discusses effective teaching and learning approaches that students have found practical. The focus includes understanding the definition of academic vocabulary, as well as methods for teaching and acquiring it effectively.